The Role of Prolactin in Assessing Luteal Phase Infertility - Channa, Sindhu; Ashraf, Razwan (Biological and Clinical Sciences Research Journal, 2025)
Luteal phase defect (LPD) is implicated in a substantial proportion of infertility cases, yet the role of circulating prolactin in luteal competence remains controversial. Although prolactin supports corpus luteum function in vitro, its utility as a clinical marker for luteal adequacy in women with regular cycles and no galactorrhea is unclear. Objective: To determine the prevalence of midluteal hyperprolactinemia among infertile women and to assess its association with luteal phase parameters, including cycle length, progesterone and estradiol levels, and endometrial histology. Methods: In this cross-sectional study, 130 infertile women aged 20–40 years with regular ovulatory cycles and no clinical hyperprolactinemia underwent basal body temperature monitoring, midluteal hormone assays, and endometrial biopsy. Plasma prolactin, progesterone, and estradiol were quantified by radioimmunoassay between four and ten days post-ovulation. Endometrial samples obtained on cycle days 21–24 were histologically staged using Noyes and Dallenbach‐Hellweg criteria; repeat biopsy was performed if initial results suggested LPD. Hyperprolactinemia was defined as prolactin above the laboratory reference range. Results: Fifteen women (11.5%) were hyperprolactinemic and 115 (88.5%) normoprolactinemic. LPD occurred in 1/15 (6.7%) hyperprolactinemic versus 20/115 (17.4%) normoprolactinemic women (p=0.13). Mean luteal phase length (13.0±1.4 vs 13.1±1.6 days), midluteal progesterone (13.3±4.8 vs 14.4±5.1 ng/mL), and estradiol (233±102 vs 227±99 pg/mL) did not differ significantly between groups. Four hyperprolactinemic women conceived spontaneously or with minimal support; others had additional infertility factors or remain under evaluation. Conclusions: Midluteal hyperprolactinemia is neither common nor predictive of luteal dysfunction in infertile women with regular cycles and no galactorrhea. A comprehensive assessment, incorporating histologic dating and steroid profiling, remains essential for accurate diagnosis of LPD and tailored infertility management